Hematological and histopathological effects of xenoestrogen (Bisphenol A) on liver and kidney functions of Mozambique tilapia fish (Oreochromis mossambicus) - Waris, Sidra; Hayat, Sikandar; Mazhar, Maham; Mahmood, Sajid (International Journal of Applied and Experimental Biology, 2023)
Xenoestrogens are chemical compounds which include phytoestrogens, polychlorinated biphenyls, bisphenol A (BPA) and phthalates, which have very serious diverse effects on fish health. The present study was designed to determine the toxicological influences of xenoestrogen BPA exposure on biochemistry and histopathology of Mozambique tilapia (Oreochromis mossambicus). The fish was exposed to sublethal concentration of BPA in aquariums for 28 days. After the completion of the trial, blood samples were taken and stored in EDTA tubes. The liver and kidney of the fish were removed and preserved in 4% formalin. After dehydration, 5 µm thick sections were cut and stained with hematoxylin. Biochemical tests such as alanine transferase (ALT), aspartate transferase (AST), total protein, blood glucose, blood creatinine, and complete blood count (CBC) were analyzed. Histological examination of kidney and liver of the control group revealed normal architecture, while the liver of the treated group showed vacuolation in hepatocytes, aggregation of lymphocytes, necrosis, increased hemorrhages, erythrocyte infiltration, and hepatocellular necrosis, while the kidney showed degeneration of glomerulus and renal tubule. Presence of melanomacrophages and hypertrophy in tubular epithelial cells increased the space in between glomerulus and enlarged Bowman’s capsule. ALT, AST, plasma glucose, WBCs, mean corpuscular volume (MCV), mean corpuscular hemoglobin concentration (MCHC) and plasma creatinine and protein values increased significantly as compared to those of the control group, while RBCs, hematocrit test (HCT) and MCH were decreased significantly.